To solve this system of linear equations, we can use the method of substitution.
First, let's solve one of the equations for one variable in terms of the other variable.
From the second equation, we can isolate x:
-x - 3y = -22
x = -22 + 3y
Now, substitute this expression for x in the first equation:
5(-22 + 3y) - 4y = -44
-110 + 15y - 4y = -44
11y = 66
y = 6
Now, substitute the value of y back into the second equation to find x:
-x - 3(6) = -22
-x - 18 = -22
-x = -22 + 18
-x = -4
x = 4
Therefore, the solution to the system of linear equations is x = 4, y = 6.
Solve the system of linear equations.
5x-4y=-44
-x-3y=-22
1 answer